Amateurs, professionals and serious leisure - Stebbins, Robert A., 1938- (McGill-Queen's University Press, 1992)
Throughout this project Stebbins has built on the work of Barney Glaser and Anselm Strauss and their notion of "grounded theory." First, Stebbins extensively observed the routine activities of amateurs and professionals in each field studied. Then, as he became more familiar with the life-styles of the participants, he conducted lengthy, unstructured, face-to-face interviews with, in most cases, thirty amateur or professional respondents. Each field demanded special methods of observation, analysis, interviewing, probing, and reporting. As much as possible, however, Stebbins asked similar questions of all respondents in all fields so as to permit generalizations across these diverse fields. The result was a "substantive grounded theory" of each field studied. In Amateurs, Professionals, and Serious Leisure, Stebbins has developed a "formal grounded theory" of amateurs and professionals based on the research accumulated in all eight substantive fields. By transcending a variety of contexts, he argues, one can gain a more enduring appreciation of the elements that affect peoples' experiences in work and leisure pursuits. A thorough review of the findings across this wide range of activities, including his findings and ideas on hobbyists and career volunteers, enabled Stebbins to derive better definitions of the main concepts of the project, such as "amateur," "the public," and "serious leisure" -- as well as "professional," where he distinguishes between client-centred and public-centred professionals who, while sharing numerous ideal-typical attributes, vary as to the power and control they have over their work in a democratic society. He presents inductive conclusions about careers and the costs and rewards in the eight amateur-professional fields considered. He examines the external world of amateurs and professionals in the light of such issues as family ties, relations among amateurs and professionals and among amateurs and their employers, public images, critics and journalists, community contributions, and the question of marginality for amateurs who are caught between the work world of the professional and the casual leisure world of the majority of the population. He concludes with an exploration of the future role of serious leisure in relation to predictions of greater unemployment and increased leisure time and longevity.